A doação de leite da perspectiva de mães em hospital de médio porte no Sertão da Paraíba - Cariry, Emmanuelle Lira (2013)
Introdution: The importance of breastfeeding is something unquestionable nowadays. For many years it is common knowledge that is the best food for infants up to 06 months old. Since ancient times, women breastfed their children and, in some occasions, helped feeding other women¿s. Human Milk Banks and their donors are, today, what net-nurses were for more than two thousand years. Objective: Identify perceptions of mothers donors of milk in a human milk bank linked to a midsize Hospital in the hinterlad of Paraiba state. Methodology: The study was conducted by a qualitative approach with 21 milk donors of the Cajazeiras Human Milk Bank. Data collection was carried out by interviews with semi-structured script. The contents of the transcriptions were submitted to analysis and the thematic nuclei found were discussed. Results: the donors were 17 to 41 years old, all of them married or in non-legal consensual marriage and the great majority living only with their companions and children, half of them with paying jobs and the other half as housewives, and the majority of them were women who had more than one children. The following thematic nuclei emerged from the analysis: Altruism or solidarity with the imaginary mother and children, shown by ""I donate to help the babies in need""; Social consciousness, avoiding waste, shown by ""I had so much milk that it was going to waste""; Empowerment of the breast, or ""the babies depend on me to be fed""; Desired pregnancy and history of loss, detected by the recurring stories of losses associated to the idea of a very precious pregnancy, ""the doctor said that it was more likely that I would have multiple abortions than giving birth to a living child""; Family support, detecting that family presence can either help (""my mother is my role model and stimulates me a lot"") or get in the way (""my mother-in-law was against it, she didn't want me to donate""); and Social support, shown from pre-natal care to the donation itself (""the nurse explained to me that it wouldn¿t lack milk to my baby, that the more you take, the more come""). Conclusion: the perceptions of mothers on milk donation were very positive, surrounded by ideas of solidarity, empathy and pride of their actions and demonstrate also that Health Promotion, from Primary Care at pre-natal care to a good welcome at the Maternity and the Human Milk Bank can be important determinants of the maintenance of breastfeeding and the decision to donate milk.